A newly growing asymptomatic facial lesion. (16th June 2022) - Butt, Sanaa; Evans, Alan; Green, Cathy; Affleck, Andrew
Abstract : A 23‐year‐old man presenting with a 1‐year history of a lesion of the right cheek. We highlight this case for awareness as this tumour may mimic other benign lesions, such as pilomatrixoma or benign cysts, as it does not have any uniquely identifying clinical or dermoscopic features. Additionally, it is of concern as malignant transformation can occur and therefore surgery should be considered as both for diagnostic and therapeutic benefit.